Transphyseal fracture-separation of the femoral capital epiphysis: a true SCFE of traumatic origin - Che Ahmad, Aminudin; Abdullah, Suhail; Shukur, Mohd Hassan; Yeap, Joo Kong (Malaysian Medical Associations, 2006)
Acute traumatic transphyseal fracture of the capital femoral epiphysis is a rare but serious injury. The injury is typically inflicted by a severe trauma. Because of the vulnerability and predisposed anatomy of the femoral epiphysis in relation to its blood supply, the fracture has been designated to have poor prognosis with inevitable osteonecrosis and eventual deformity of the hip. We report a case of such fracture in a 13-year-old child in view to highlight some of the anticipated problems in the management of such injury.